PARTISIPASI MASYARAKAT DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN DI KELURAHAN MAMBORO KECAMATAN PALU UTARA - Sanjaya, Roy Topan (Katalogis, 2013)
This research aims knowing the community participation in development plan meeting in Kelurahan Mamboro, subdistrict of North Palu. Ericson’s theory on participations used in this study consist of participation, and participation during the period of use. This research employs qualitative design. Informants of this research are head of Mamboro subdistrict, the head of economic and Development Section, the head of Community Empowerment Institution and Community that are sampled using purposive technique. While technique of data collection of this research includes observation, in-depth interview and documentation, the technique of data analysis includes data reduction, data presentation, and inference or verification. The result that community participation in development plan meeting is still low. The community seems to be active in pre-meeting. However they tend to criticize and to question the meeting that does not give any significant contribution to them. Community participation during program implementation also seems very low. They were not included in the process of implementation rather the government does all parts of the work. Community during this period takes a role only as controller of development process. Community participation during the period of use is also very low They are still lack of awareness to maintain the development result, and this type of attitude will become and obstacle for the development process.